THE FOUNDING AND FIRST YEARS OF ACTIVITY OF NAGYVÁRADI ATLÉTIKAI CLUB FOOTBALL TEAM 1910 – 1914 - LUKÁCS, Norbert Csaba (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2021)
The year 2020 marks one hundred and ten years since the founding of Nagyváradi Atlétikai Club (in Romanian: Clubul Atletic Oradea), which in matter of football was one of the reference sports groups in the city of Nagyvárad in the first half of the 20th century. Due to this anniversary, we set out to present the history of this team, from the moment when it was founded up to the outbreak of World War I. Through its contents, this paper contributes to a better understanding of the past of this sports team and, in the same time, it represents an acclaim of its founders, leaders and players. The first part of this paper presents the founding of Nagyváradi Atlétikai Club team, its first years of activity, its attendance to competitions, international matches, its contribution to shaping iconic players for local football and for the national teams of Hungary and Romania, and then it presents the headquarters, playing fields, coaches and main leaders of the team. Through its contents, this paper is of interest, not only for those who just want to expand their general knowledge, but also for people who study Nagyvárad’s football history. REZUMAT. Constituirea și primii ani de activitate a echipei de fotbal Nagyváradi Atlétikai Club 1910 – 1914. În anul 2020 s-au aniversat o sută zece ani de la constituirea echipei de fotbal Nagyváradi Atlétikai Club care a fost una dintre grupările sportive de referință ale fotbalului din orașul Nagyvárad în prima jumătate a secolului al XX-lea. Având în vedere acest moment aniversar, ne-am propus să prezentăm istoria acestei echipe, începând cu înființarea ei și până la izbucnirea Primului Război Mondial. Prin conținutul său, lucrarea contribuie la mai buna cunoaștere a trecutului acestei formații sportive și, în același timp, reprezintă o recunoaștere a celor care au înființat echipa, a conducătorilor și a jucătorilor ei. În prima parte, lucrarea se referă la constituirea echipei Nagyváradi Atlétikai Club, primii săi ani de activitate, participarea ei în competiții, meciurile sale internaționale, contribuția la formarea unor jucători reprezentativi pentru fotbalul local și pentru selecționatele Ungariei și cea a României, apoi prezintă sediile, terenurile, antrenorii și conducătorii săi mai importanți. Prin conținutul său, lucrarea prezintă interes, atât pentru cei care doresc doar să-și lărgească aria de informare, dar și pentru cei care studiază trecutul fotbalului orașului Nagyvárad. Cuvinte cheie: Nagyváradi Atlétikai Club, Clubul Atletic Oradea, fotbal.